Proteomic and Single-Cell Transcriptomic Dissection of Human Plasmacytoid Dendritic Cell Response to Influenza Virus - Ghanem, Mustafa H.; Shih, Andrew J.; Khalili, Houman; Werth, Emily G.; Chakrabarty, Jayanta K.; Brown, Lewis M.; Simpfendorfer, Kim R.; Gregersen, Peter K. (Frontiers in Immunology, 2022)
Plasmacytoid dendritic cells [pDCs] represent a rare innate immune subset uniquely endowed with the capacity to produce substantial amounts of type-I interferons [IFN-I]. This function of pDCs is critical for effective antiviral defenses and has been implicated in autoimmunity. While IFN-I and select cytokines have been recognized as pDC secreted products, a comprehensive agnostic profiling of the pDC secretome in response to a physiologic stimulus has not been reported. We applied LC-MS/MS to catalogue the repertoire of proteins secreted by pDCs in response to challenge with live influenza H1N1. Additionally, using single-cell RNA-seq [scRNA-seq], we perform multidimensional analyses of pDC transcriptional diversification following stimulation. Our data reveal an abundance of protein species released by pDCs in addition to IFN-I, and evidence highly specialized roles within the pDC population ranging from dedicated cytokine super-producers to cells with APC-like functions. Moreover, dynamic expression of transcription factors and surface markers characterize activated pDC fates.